Vegetable and Fruit Intakes Are Associated with hs-CRP Levels in Pre-Pubertal Girls - Navarro, Pilar (Nutrients, 2017)
The influence of diet on inflammation in children remains unclear. We aimed to analyze the influence of diet on high-sensitivity C-reactive protein (hs-CRP) levels in a pre-pubertal population free of other influences that may affect hs-CRP levels. We determined hs-CRP levels in 571 six- to eight-year-old children using an hs-CRP ELISA kit. Information on food and nutrient intake was obtained through a food-frequency questionnaire. Overall dietary quality was assessed using the Healthy Eating Index (HEI). We found that girls in the highest tertile of hs-CRP levels had a higher intake of saturated fatty acid, and lower intakes of fiber and vitamin E and a lower HEI score when compared to those in tertiles 1 and 2. We also observed a significant decrease in fruit and vegetable intakes by hs-CRP tertile. Factor analysis showed that a dietary pattern that was loaded most strongly with vegetable, fruit, fiber and vitamin A and E intakes correlated negatively (−0.132, p < 0.05) with hs-CRP. No such association was found in boys. In conclusion, our data show that girls with a poorer quality diet show higher hs-CRP levels already at a pre-pubertal age.